Christian joy - Williams, Denis Ivor (Rhodes University, Faculty of Divinity, Department of Divinity, 1980)
Christian joy is identified by linguistic and symbolic, experiential and psychological studies, and by a study of its opposite, sorrow. The final and most comprehensive approach is Biblical and theological. Here, through Judaism and Christianity, the genesis and fulfilment of Christian joy is examined, in life and the gifts of God, in hope, and in union with God. It is defined as "a gift of God's Holy Spirit as man becomes one with Christ in love." Five hypotheses are evaluated and confirmed: - 1. God is perfect joy, 2. God is the source and end of all Christian joy, 3. Jesus Christ is both the most joyful and the most sorrowful of men, 4. The Christian participates in the joy and sorrow of Jesus Christ, 5. Christian joy is eschatological in nature. The need is stressed for a fuller understanding and expression of Christian joy, which is seen as the complement of Christian love, and as a distinguishing characteristic of Christians, because of its primary intentional and ultimate satisfactory nature
Keywords: Joy -- Religious aspects -- Christianity; Christian life